A Light-Oxygen-Voltage Receptor Integrates Light and Temperature. Issue 15 (23rd July 2021) - Dietler, Julia; Schubert, Roman; Krafft, Tobias G.A.; Meiler, Simone; Kainrath, Stephanie; Richter, Florian; Schweimer, Kristian; Weyand, Michael; Janovjak, Harald; Möglich, Andreas
Graphical abstract: Highlights: Coupling to photoreceptor modules allows optogenetic control of cellular processes. Dimeric light-oxygen-voltage (LOV) domains bestow light control on the Tet repressor. Rs LOV from Rhodobacter sphaeroides confers sensitivity to both light and temperature. Two Rs LOV variants with improved stability and affinity overcome the thermosensitivity. Light-responsive Tet repressor variants enable precision control of gene expression. Abstract: Sensory photoreceptors enable organisms to adjust their physiology, behavior, and development in response to light, generally with spatiotemporal acuity and reversibility. These traits underlie the use of photoreceptors as genetically encoded actuators to alter by light the state and properties of heterologous organisms. Subsumed as optogenetics, pertinent approaches enable regulating diverse cellular processes, not least gene expression. Here, we controlled the widely used Tet repressor by coupling to light-oxygen-voltage (LOV) modules that either homodimerize or dissociate under blue light. Repression could thus be elevated or relieved, and consequently protein expression was modulated by light. Strikingly, the homodimeric Rs LOV module from Rhodobacter sphaeroides not only dissociated under light but intrinsically reacted to temperature. The limited light responses of wild-type Rs LOV at 37 °C were enhanced in two variants that exhibited closely similar photochemistry and structure. One variant improved the weak homodimerization affinity of 40 µM by two-fold and thus also bestowed light sensitivity on a receptor tyrosine kinase. Certain photoreceptors, exemplified by Rs LOV, can evidently moonlight as temperature sensors which immediately bears on their application in optogenetics and biotechnology. Properly accounted for, the temperature sensitivity can be leveraged for the construction of signal-responsive cellular circuits.